Peran Consumer Perceived Value dalam Online Review terhadap Impulse Buying Tendency melalui Browsing sebagai Variabel Intervening - Evi Mardian Ningsih; Anik Lestari Andjarwati (Jurnal Ilmu Manajemen, 2021)
Shopee is one of the favourable marketplaces in Indonesia. This research investigates impulse buying among Shopee user. In addition, it also analyzes the relationship between practical value, hedonic value, browsing, and impulse buying tendency. The survey was conducted using an online questionnaire and collected data from 211 respondents, the Shopee marketplace application users. Analysis of Structural Equation Modeling (SEM) in the Partial Least Square (PLS) program is used to analyze the data. The results show that the utilitarian value does not affect impulse buying tendency via browsing, and hedonic value affects impulse buying tendency via browsing. This research has limitations, which are: this research only involves the Shopee marketplace, so it is possible that it cannot be generalized to all types of marketplaces, and for further investigation, it can add or compare other marketplaces such as Tokopedia, Lazada, and Blibli. Supposedly, this study calls other variables, such as expressive value, sacrifice value, web quality, and purchase intention.